Slope instability context in the National Route 613 in 2020, Coto Brus, Costa Rica - Sequeira Arguedas, Jose María (2025)
At this investigation, it is characterized the slope unstability along the 613 national road located in Coto Brus county, Costa Rica, triggered by intense precipitation between November the 1st and the 6th related to Eta’s hurricane pathway. By stablishing the geological, geomorphological and hydroclimatic context, besides field annotations, landslide inventory and geospatial inputs, it is proposed a road zonation in stable and landslide prone sections of the mountain corridor. The integration of all these methods allows to determine that, at least 24 % of the road is prone to slope unstability with a clear influence of geological tectonic features. In addition, there are hydroclimatic and hydrometeorological features (long and short period modulators, respectively) that could trigger hillslope unstability along the road corridor in the near future, by the development of extreme precipitation events every rainy season on Costa Rica’s southern Pacific, without excluding possible superficial seismic rupture scenarios at one of the five active fault traces that crosses the road corridor.